Alcohol use and poor sleep quality: a longitudinal twin study across 36 years. Issue 1 (6th July 2022) - Helaakoski, Viola; Kaprio, Jaakko; Hublin, Christer; Ollila, Hanna M; Latvala, Antti
Abstract: Study Objectives: Poor sleep is one of the multiple health issues associated with heavy alcohol consumption. While acute effects of alcohol intake on sleep have been widely investigated, the longitudinal associations remain relatively underexplored. The objective of our research was to shed light on cross-sectional and longitudinal associations between alcohol use and poor sleep quality over time, and to elucidate the role of familial confounding factors in such associations. Methods: Using self-report questionnaire data from the Older Finnish Twin Cohort (N=13, 851), we examined how alcohol consumption and binge drinking are associated with sleep quality during a period of 36 years. Results: Cross-sectional logistic regression analyses revealed significant associations between poor sleep and alcohol misuse, including heavy and binge drinking, at all four time points (OR range =1.61-3.37, P <0.05), suggesting that higher alcohol intake is associated with poor sleep quality over the years. Longitudinal cross-lagged analyses indicated that moderate, heavy and binge drinking predict poor sleep quality (OR range =1.25-1.76, P <0.05), but not the reverse. Within-pair analyses suggested that the associations between heavy drinking and poor sleep quality were not fully explained by genetic and environmental influences shared by the co-twins. Conclusions: In conclusion, our findings support previous literature in that alcohol use is associated with poor sleep quality, such that alcohol use predicts poor sleep quality later in life, but not vice versa, and that the association is not fully explained by familial factors.